2018
DOI: 10.1007/s40200-018-0335-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a store-and-forward telescreening system of diabetic retinopathy: lessons learned from Iran

Abstract: Background The present study describes the development and identity phases of a teleophthalmology system used for screening of diabetic retinopathy. Methods A questionnaire was used to identify the main factors necessary for diagnosis of diabetic retinopathy and the features required for a teleophthalmology system. In the second phase, a web-based prototype of the system was designed using the data collected in the previous phase. In the final phase, the system was optimized based on the users' ideas and comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…It was possible to transfer the data via web and receive immediate online diagnosis [ 25 , 29 ]. There was also a special teleretinal screening software platform used [ 16 , 22 , 26 , 27 , 29 , 30 , 35 , 37 , 44 , 47 , 51 , 54 , 56 , 59 , 65 67 , 69 , 70 , 72 , 75 , 81 , 97 ] or, alternatively, access to all information could be obtained through a special account on a medical platform.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was possible to transfer the data via web and receive immediate online diagnosis [ 25 , 29 ]. There was also a special teleretinal screening software platform used [ 16 , 22 , 26 , 27 , 29 , 30 , 35 , 37 , 44 , 47 , 51 , 54 , 56 , 59 , 65 67 , 69 , 70 , 72 , 75 , 81 , 97 ] or, alternatively, access to all information could be obtained through a special account on a medical platform.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Xiao et al presented a comprehensive teleretinal eye treatment plan with SMS [short messaging service] patient information on the date of eye examination. To improve the quality of telescreening, internal self-checking of image system quality was assessed [ 99 ], and a development scheme was used to design a DR telemedicine screening program [ 37 ]. To improve access to DR screening, local women’s self-help groups were tasked with its implementation [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the previous sections, the usability of the final version of the teleoncology system was evaluated by using the QUIS questionnaire. Similarly, some researchers in their studies have used the QUIS questionnaire to evaluate the usability of telemedicine systems [ 43 , 56 , 57 ]. In addition, some studies have used the System Usability Scale (SUS) questionnaire to assess usability [ 46 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final list of articles showed that the Telehealth Usability Questionnaire (TUQ) (n = 10, 19%) [10][11][12][13][14][15][16][17][18][19] and Telemedicine Satisfaction Questionnaire (TSQ) (n = 7, 13%) [20][21][22][23][24][25][26] were the most commonly used. Then, the Service User Technology Acceptability Questionnaire (SUTAQ) (n = 3, 5.5%) [27][28][29], the Client Satisfaction Questionnaire (CSQ) (n = 3, 5.5%) [30][31][32], the Questionnaire for User Interaction Satisfaction (QUIS) (n = 3, 5.5%) [33][34][35], the System Usability Scale (SUS) questionnaire (n = 3, 5.5%) [36][37][38], the Patient Satisfaction Questionnaire (PSQ) (n = 3, 5.5%) [22,39,40], the Telemedicine Satisfaction and Usefulness Questionnaire (TSUQ) (n = 2, 3.5%) [41,42], the Patient Assessment of Communication during Telemedicine (PACT) questionnaire (n = 2, 3.5%) [43,44], the Post Study System Usability Questionnaire (PSSUQ) (n = 2, 3.5%) [19,45] and the Technology Acceptance Model (TAM) (n = 2, 3.5%) [46,47] were the most used questionnaires, respectively. The rest of the articles had used other questionnaires (n = 18, 34%)…”
Section: Evaluation Questionnairementioning
confidence: 99%